History and Contributions of Hadharatul Islamiyah Islamic Boarding School in Community Development in Sipispis District Serdang Bedagai Regency, 2009-2023 - Purba, M. Zuhri Wanda; Naldo, Jufri (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This research investigates the role of Pondok Pesantren Hadharatul Islamiyah in Sipispis Subdistrict, Serdang Bedagai Regency from 2009 to 2023, employing a qualitative descriptive method and a historical approach. The study focuses on the pesantren's involvement in education, religious affairs, and socio-community aspects. The findings highlight the pivotal role of the pesantren in religious education, serving as a platform for students to deepen their understanding of Islam. Moreover, the pesantren contributes to molding the community's character by instilling Islamic values. Economically, it empowers the community through skill-building initiatives and fosters economic self-sustainability. Additionally, the pesantren fosters social awareness and tolerance among residents by promoting positive social ethics. This research offers a comprehensive understanding of the pesantren's impact on community development, providing insights that can inform further efforts to enhance its role and promote regional development.